Texture analysis of dried papaya (Carica papaya L., cv. Maradol) pretreated with calcium and osmotic dehydration. Issue 7 (19th May 2019) - Barragán-Iglesias, Josué; Rodríguez-Ramírez, Juan; Sablani, Shyam S.; Méndez-Lagunas, Lilia L.
Abstract: The application of pretreatments before to convective drying improves the textural characteristics of minimally processed fruits. The aim of this work was to evaluate the texture of papaya ( Carica papaya L., cv. Maradol) dried by convection pretreated with calcium hydroxide solutions and osmotic dehydration. Texture profile analysis was performed on fresh and dried cubes by convection at 70 °C not pretreated, as well as on those pretreated with calcium and osmotic solutions. During calcium immersion, the firmness increased, the TSS decreased, and the calcium gain was higher to low temperature. Water loss and solids gain were higher using high concentrations and temperatures during osmosis, resulting in lower values of moisture content and higher values ​​of TSS. Calcium and osmotic pretreatments resulted in a product with intermediate moisture, stable color, firm, and minimal shrinkage. The modification of the papaya structure during all treatments caused a change in the textural characteristics. Statistical analysis of textural characteristics of dry cubes pretreated showed a significant difference ( α = 0.05) compared to fresh ones and not pretreated. The pretreatments formed a firm (outer) and a soft (inside) structure that reduced the shrinkage and the deformation of dry cubes and decrease the drying time up to 37% compared to dry cubes no pretreated.